Primary Endpoints in Pediatric Efficacy Trials Submitted to the US FDA - Green, Dionna J; Burnham, Janelle M; Schuette, Paul; Liu, Xiaomei I; Maas, Brian M; Yao, Lynne; McCune, Susan K; Chen, Joseph; van den Anker, John N; Burckart, Gilbert J (Journal of clinical pharmacology, 2018)
The selection of appropriate endpoints in pediatric drug development trials is a critical aspect of trial design. Given the high pediatric trial failure rate, selecting optimal trial design elements, such as the primary efficacy endpoint, is essential to ensuring increased potential for trial success. The objectives of this study were to identify the primary efficacy endpoints measured in pediatric drug development trials submitted to the US Food and Drug Administration and to relate endpoint attributes to trial and label outcome. The analysis included pediatric pivotal efficacy studies submitted from September 2007 to July 2016 for which there was a corresponding adult trial for the same indication. Two hundred and thirty-four efficacy trials on 138 unique products studied in pediatric patients were assessed. The adult and pediatric endpoints were the same in 141 of the 234 trials (60.3%), and these trials succeeded in meeting their primary endpoint more often (122 of 141 [86.5%]) than when the adult and pediatric endpoints differed (57 of 93 [61.3%]; odds ratio, 4.03; 95%CI, 2.10-7.80). Trials that included both pediatric and adult patients succeeded more frequently than those trials that did not combine pediatric and adult patients (85 of 95 versus 94 of 139, respectively; odds ratio, 4.05; 95%CI, 1.94-9.31). No differences were observed in pediatric trial success between those using subjective and objective endpoints. Using the same endpoint in the pediatric trial as was measured in the corresponding adult trial and enrolling pediatric and adult patients in the same trial were attributes associated with trial success.